Structural Behavior of SCC Hollow Beam Reinforced with GFRP Containing EPS and Plastic Fiber - Abduljaleel, Mohanad T.; Al-Hadithi, Abdulkader Ismail (Iraqi Journal of Civil Engineering, 2025)
The purpose of this research is to produce a modified SCC that involves the incorporation of expanded polystyrene (EPS) and waste of plastic type (PET). The goal is to minimize the weight of the material while simultaneously improving its brittleness and reducing the environmental impact. The study focuses on two methods for reducing the weight of structural elements by using EPS beads, which create voids through concrete, and the second method is making a hollow through the element. This study included designing and investigating four concrete beams under concentrated static load. The parameters were hollow position and material types. The results showed that the offsetting hollow from the center of the beam enhanced the ductility index by 10% and increased the load capacity by 10%. Adding EPS beads reduce the concrete density by 11.5% and load capacity by 22%. Toughness was improved by using plastic fiber due to the mechanism of crack bridging. The crack pattern had been changed due to the utilization of waste material, and enhancement was observed through experimental tests by making smooth cracks and changing the probability of sudden failure when using GFRP rebars. It was found that the optimal quantity of EPS was 2 kg to produce SCC in accordance with code requirements. No debonding or slip was observed during monitoring, as evidenced by the absence of spalling or cracking around the reinforcement.